Endolymphatic Hydrops in Patients With Vestibular Migraine and Concurrent Meniere's Disease - Oh, Sun-Young; Dieterich, Marianne; Lee, Bit Na; Boegle, Rainer; Kang, Jin-Ju; Lee, Na-Ri; Gerb, Johannes; Hwang, Seung-Bae; Kirsch, Valerie (Frontiers in Neurology, 2021)
Objective: Intravenous contrast agent enhanced, high-resolution magnetic resonance imaging of the inner ear (iMRI) confirmed that patients with Menière's disease (MD) and vestibular migraine (VM) can present with endolymphatic hydrops (EH). The present study aimed to investigate EH characteristics and its interrelation to neurotologic testing in patients with VM, MD, or VM with concurrent MD (VM-MD). Methods: Sixty-two patients (45 females, aged 23–81 years) with definite or probable VM (n=25, 19 definite), MD (n=29, 17 definite), or showing characteristics of both diseases (n=8) were included in this study. Diagnostic workup included neurotologic assessments including video-oculography (VOG) during caloric stimulation and head-impulse test (HIT), ocular and cervical vestibular evoked myogenic potentials (o/cVEMP), pure tone audiometry (PTA), as well as iMRI. The degree of EH was assessed visually and via volumetric quantification using a probabilistic atlas-based segmentation of the bony labyrinth and Volumetric Local Thresholding (VOLT). Results: Although a relevant number of VM Patients reported varying auditory symptoms (13 of 25, 52.0%), EH in VM was only observed twice. In contrast, EH in VM-MD was prevalent (2/8, 25%) and in MD frequent (23/29, 79.3%; χ2(2)= 29.1, p<0.001, φ=0.7). Location and laterality of EH and neurophysiological testing classifications were highly associated (Fisher exact test, p<0.005). In MD, visual semi-quantitative grading and volumetric quantification correlated highly to each other (rS =0.8, p<0.005, two-sided) and to side differences in VOG during caloric irrigation (vestibular EH ipsilateral: rS=0.6, p<0.05, two-sided). In VM, correlations were less pronounced. VM-MD assumed an intermediate position between VM and MD. Conclusion: Cochlear and vestibular hydrops can occur in MD and VM patients with auditory symptoms; this suggests inner ear damage irrespective of the diagnosis of MD or VM. The EH grades often correlated with auditory symptoms such as hearing impairment and tinnitus. Further research is required to uncover whether migraine is one causative factor of EH or whether EH in VM patients with auditory symptoms suggests an additional pathology due to MD.